A Rare Cause of Occult Gastrointestinal Bleeding: Solitary Rectal Ulcer Syndrome - Azar Abiyev; İbrahim Doğan (Caucasian Medical Journal)
Occult gastrointestinal (GI) bleeding is defined as iron deficiency anemia or positive fecal guaiac test results without obvious bleeding. There are multiple reasons for occult GI bleeding. Despite its rarity, solitary rectal ulcer syndrome (SRUS) can result in occult bleeding. Here we will discuss a case of SRUS.